FBXW7 metabolic reprogramming inhibits the development of colon cancer by down-regulating the activity of arginine/mToR pathways - Qing Li; Yan Li; Tong Zhou; Yong Zhang; Huiyu Li; Fajia Yuan; Yanghui Bi (PLoS ONE, 2025)
FBXW7 is a tumor suppressor gene that regulates metabolism and is associated with the onset and progression of colorectal cancer (CRC)), however, the precise mechanism whereby FBXW7 participates in the metabolic reprogramming of CRC remains unclear. Here, the research aims to reveal the association between the expression of FBXW7 and clinical variables and to investigate the molecular mechanism by which FBXW7 plays a critical role in the development of CRC. The clinical importance of FBXW7 in CRC was determined by immunohistochemistry. Non-targeted metabolomics was utilized to explore the role of FBXW7 in the metabolic regulation of CRC. Low expression of FBXW7 was associated with poor prognosis in individuals with CRC, both at the mRNA and protein levels. FBXW7 over-expression inhibited CRC cell growth, colony formation, migration, and invasion. Non-targeted metabolomics unveiled that FBXW7 over-expression directly caused the deprivation of arginine which led to downmodulation of mTOR signaling pathway; meanwhile, FBXW7-related metabolites were primarily concentrated in the mTOR signaling pathway. In summary, the research identified a novel mechanism of action of FBXW7 in CRC. The research findings provide a theoretical foundation for the prognostic prediction and therapeutic planning of CRC based on metabolic reprogramming.